Reframing Patient’s Autonomy in End-of-Life Care Decision-Making: Constructions of Agency in Interviews with Physicians - Buscariolli, André; Vesala, Kari Mikko (Qualitative Sociology Review, 2021)
In the research literature, critical viewpoints question the idea of patient autonomy as a robust basis for approaching end-of-life treatments. Yet physicians express distinctly positive attitudes towards patient autonomy and advance directives in questionnaire studies. In this article, we unravel taken-for-granted assumptions about the agency that physicians use when evaluating patient autonomy in end-of-life care. We use Goffmanian frame analysis to analyze semi-structured interviews with eight Finnish physicians. Instead of measuring standardized responses, we explore in detail how distinct evaluations of patient autonomy are made through approving or reserved stand-taking. The results show that the interviewees reframed patient autonomy with the help of biological, medical, ethical, and interaction frames. Through such reframing, the patient’s agency was constructed as vulnerable and weak in contrast to the medical expert with the legitimated capacity to act as an agent for the patient. Further, end-of-life treatment decisions by the patient, as well as the patient’s interests appeared as relationally defined in interactions and negotiations managed by the physician, instead of attesting the sovereign agency of an autonomous actor.